Effects of Copper Minerals on Ammoniacal Thiosulfate Leaching of Gold (International Mineral Processing Congress, 2014)
Cyanide is reactive to copper minerals and is not suitable to extract the gold from the copper bearing ores. Ammoniacal thiosulfate is considered an excellent alternative lixiviant for leaching copper bearing gold ores. Unfortunately the results of high reagent consumption and poor gold ex-traction were found by thiosulfate leaching of synthetic gold ores containing chalcopyrite, chalcocite or bornite and a mild refractory copper-bearing sulfidic gold ore. In this investigation, several processes have been applied to reduce the impacts of these minerals on gold leaching. The process included: the pre-oxidation of copper sulphide minerals in water or ammonia solution, the reduction of dissolved oxygen in the lixiviant (0.3 ppm DO or 0.7% oxygen), adding phosphate anion in the leach or pre-leach stage, and the addition of a strong copper ligand (e.g., EDA and DETA). The results indicated that the gold extraction could be improved to 93% with the thiosulfate consumption being reduced to less than 8 kg/t. The dissolution of copper minerals was found to be the major reason for increased consumption of thiosulfate and the highly reductive leached surfaces are responsible for the reduced gold extractions.